Factors Affecting English Speaking Skills and Attitudes of Students Majoring in Teaching English at the Faculty of Education, Souphanouvong University: https://doi.org/10.69692/SUJMRD24.9.1.295-303 - LAMPHAIPHANH, Ketsalinh; SIDAVONG, Khanthaly; SISOMBATH, Sithonh (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The four basic skills of learning a language (listening, speaking, reading and writing) are essential in real-life communication; however, speaking has been a challenge to numerous EFL learners in non-native speaking nations, such as Thailand, Indonesia and Saudi Arabia. The present study aims at investigating the factors affecting English speaking skills and attitudes for students majoring in teaching English at the Faculty of Education, Souphanouvong University, Lao PDR. It looks at the factors that affect students’ English-speaking skills and attitudes, and discusses some possible strategies that might help to improve students’ speaking skills. The instrument was a questionnaire using a 5-point Likert scale, which covered student, teacher, curriculum, school environment and social factors. It was distributed to 53 students of English in years 2, 3 and 4, who were selected as the population sample. There were 24 male and 29 female participants. SPSS was employed to analyze the data and indicate the results in descriptive tables. The results revealed that the key factors that affected the students’ speaking skills were classroom temperature and noise, with means of 3.96 and 3.78, respectively. Other factors among the 10 top-ranked included the student factors of not knowing the right vocabulary words (mean of 3.69), not knowing what to say (3.5), and not being self-confident (3.49); the curriculum factor of too many subjects being taught in the Lao language (3.67); and the social factors of not learning English as a child (3.67) and of not knowing enough about the background culture (3.63).